Efficiency enhancement of the modified EWMA control method with conditional expected delay for change detection in processes - Khan, Nasrullah; Aslam, Muhammad; Albassam, Mohammed (Frontiers in Applied Mathematics and Statistics, 2023)
This study investigates the efficiency of a modified exponentially weighted moving average (EWMA) control method using conditional expected delay to improve its efficiency in detecting changes in a process over time. While the modified EWMA control method is commonly used for this purpose, it can sometimes experience delays in detecting changes. The proposed method aims to address this limitation by incorporating conditional expected delay. The study utilizes simulations to conduct a performance comparison between the modified EWMA control method and the conventional EWMA control, employing the metric of conditional expected delay.Simulation results demonstrate that the modified EWMA control method with conditional expected delay in terms of accurately and rapidly detecting changes. Overall, this study concludes that the integration of conditional expected delay into the modified EWMA control method can increase its effectiveness in detecting changes in a process. This has significant practical implications for a variety of industries that require timely and accurate detection of changes to maintain product quality and optimize processes.